A Reflection on Dynamics of Teacher Competence to Cope with Post- Pandemic Teaching in Indonesia - Yulia Hapsari; Emi Emilia (FKIP Universitas Lampung, 2024)
A Reflection on Dynamics of Teacher Competence to Cope with Post-Pandemic Teaching in Indonesia. Objective: This paper aims to describe Indonesian teachers' competence in coping with the COVID-19 pandemic through their self-reflection and satisfaction with their teaching practices during the pandemic. Methods: A cross-sectional online survey using snowballing sampling was employed. Findings: This study found that from 111 teachers from various provinces in Indonesia participated in the survey, dynamic modifications in the teacher competencies, especially in the pedagogical and social competencies were apparent. Overall, while pedagogical competence experienced a decrease, social competence increased, whereas personality and professional competencies stayed the same. The volatile, uncertain, complex, and ambiguous (VUCA) conditions during the pandemic indicated facilitation in improving teacher competencies, primarily in the teachers ’ ability to integrate ICT into their teaching practices. However, the VUCA situation also recedes the teachers' competencies in understanding their learners (pedagogical competence), in being democratic and reasonable (personality competence), and in socializing with students and colleagues (social competence). Therefore, adaptive teaching and social-emotional competencies are crucial for teachers to manage post-pandemic teaching. Conclusion: These results should inform the importance of accommodating the VUCA framework in teacher competence to deal with new standards in education. Keywords: distance learning, ICT in ELT, teacher competencies, new normal education, VUCA circumstances.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202471